Implementation of a User-Friendly, Flexible Expert System for Selecting Optimal Set of Kidney Exchange Combinations of Patients in a Transplantation Center - Karademirci, O.; Terzioğlu, A.S.; Yılmaz, S.; Tombuş, Ö. (Transplantation proceedings, 2015)
For end-stage renal disease patients, kidney transplantation is the only long-term solution. The number of deceased donors is limited. Living kidney donation is subject to strict regulations, limiting possible donors only to the extended family of the patient for preventing the organ trade. There may be incompatibilities between the patients and their related donors, such as ABO blood type incompatibility, positive cross-match, and so on. Pairwise exchanges between donors and recipients increase both the quality and the quantity of feasible transplantations. The maximum benefit in kidney exchanges could only be yielded by developing a central kidney exchange program supported by a nation wide living donor pool database. In the absence of a central kidney exchange program, each transplantation center arranges the kidney allocations using spreadsheets manually. Selecting best possible combination of exchanges simultaneously is a difficult task when performed manually. It is a proven NP-Hard combinatorial optimization problem. However, using mixed integer programming methods the best combination can be found in seconds. We developed a user-friendly decision support system that can be used in transplantation centers, facilitating their operations. The decision support system can be modified for according to the matching preferences of transplantation centers and it can be used as a simulation tool for analyzing different allocation methods.